-6x-9+2x=39

Simple and best practice solution for -6x-9+2x=39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-9+2x=39 equation:


Simplifying
-6x + -9 + 2x = 39

Reorder the terms:
-9 + -6x + 2x = 39

Combine like terms: -6x + 2x = -4x
-9 + -4x = 39

Solving
-9 + -4x = 39

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -4x = 39 + 9

Combine like terms: -9 + 9 = 0
0 + -4x = 39 + 9
-4x = 39 + 9

Combine like terms: 39 + 9 = 48
-4x = 48

Divide each side by '-4'.
x = -12

Simplifying
x = -12

See similar equations:

| (3t^2-t-4)(4t^2+3t-1)= | | 2x+5+3x=-25 | | 3(13+5.5k)=6k+18 | | 33=-4x-3x-2 | | -2-3x-4x=33 | | Cot^4x-1=0 | | 2-3x-4x=33 | | 2x^2+6y^2=13 | | 49/7p-49 | | 4[lnz+ln(z+5)]-2ln(z-5)= | | h=-16t*t+128t | | 4+6x+6x=-44 | | 1+7x+2x=109 | | 7(c-9)=9(2c-8)-4c | | 9x^6y^10/x^0Y^9 | | y=a^8+cos^8x | | n=c-m | | 3t+nt=y | | -4x+9+5x=18 | | 56=7/8v | | 10=(1/6)x | | 2x-5+5x=-54 | | 10p^3-25p^2+4p-10=0 | | y=4x^2-8 | | 2x-5+2x=23 | | (2x+5)x=420 | | 5x-6+5x=64 | | x-9+0.5=180 | | 3.75-7.1= | | 3.75+7.1= | | 2(2x+13)+8=6 | | 7=x+1+2x-3 |

Equations solver categories